Marriage in Honey Bees Optimization Algorithm for Flow-shop Problems - Pedro PALOMINOS; Francisco TOLEDO; Andrés VÉJAR; Miguel ALFARO (Informatică economică, 2012)
The objective of this work is to make a comparative study of the Marriage in Honeybees Op-timization (MBO) metaheuristic for flow-shop scheduling problems. This paper is focused on the design possibilities of the mating flight space shared by queens and drones. The proposed algorithm uses a 2-dimensional torus as an explicit mating space instead of the simulated an-nealing one in the original MBO. After testing different alternatives with benchmark datasets, the results show that the modeled and implemented metaheuristic is effective to solve flow-shop type problems, providing a new approach to solve other NP-Hard problems.